1988
DOI: 10.1007/bf01849438
|View full text |Cite
|
Sign up to set email alerts
|

The Copper-Fix (Cu-Fix): a new concept in IUD technology

Abstract: The Copper-Fix (Cu-Fix) is a thread-type copper-bearing device designed to overcome the most common IUD-related problems: bleeding and pain. Two distinctive features--virtual absence of a frame and provision of an anchoring system--make this new intrauterine device the first radical departure from current IUD technology. The Cu-Fix 390 was inserted at intervals in 382 women, and 4851 woman-months of experience had been accumulated at 18 months. The device was exceedingly well retained by the uterus (expulsion … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

1991
1991
2011
2011

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 27 publications
(9 citation statements)
references
References 2 publications
0
9
0
Order By: Relevance
“…At the end of 12 months of use, the pregnancy rate was 0.3 (based on a single pregnancy, probably due to an unnoticed expulsion), the expulsion rate was 0.6, and the removal rate for bleeding and/or pain was 3.1. The one-year continuation rate was 94.2 [6]. Batar conducted a noncomparative study of 344 women using the Flexigard-330, and showed similarly favorable results [17].…”
Section: Performance Of the New Devicesmentioning
confidence: 75%
See 3 more Smart Citations
“…At the end of 12 months of use, the pregnancy rate was 0.3 (based on a single pregnancy, probably due to an unnoticed expulsion), the expulsion rate was 0.6, and the removal rate for bleeding and/or pain was 3.1. The one-year continuation rate was 94.2 [6]. Batar conducted a noncomparative study of 344 women using the Flexigard-330, and showed similarly favorable results [17].…”
Section: Performance Of the New Devicesmentioning
confidence: 75%
“…The following analyses compare the performances of the CU-SAFE [5], Cu-Fix [6,17], Ombrelle [7,19], and Fincoid IUDs [20] (S Kaivola, personal communication) with the TCu380A, an IUD whose reputation for excellent performance is well-established. The study by Sivin and Tatum reported in 1981 was used as an historical comparison [21] (Table 1).…”
Section: Comparisons With the Tcu380amentioning
confidence: 99%
See 2 more Smart Citations
“…Significant reasons for discontinuation were expulsion, bleeding and/or pain. 20 The initial trials with the frameless IUD conducted in Belgium, and later internationally, in parous and nulliparous women, were promising 21,22 . However, the WHO randomised clinical trial comparing the TCu380A with the frameless Flexigard 1 IUD (Flexigard 1 , developed by GynoPharma, Inc. in the USA, uses the same frameless design as that of the current GyneFix 1 IUD but a different inserter), involving parous women only, did not show a difference in removal rate for bleeding and pain 23 .…”
Section: F R a M E L E S S I N T R A U T E R I N E C O N T R A C E P mentioning
confidence: 98%